Improvement of lecturer performance in research and scientific publication through coaching program at Marsekal Suryadarma Aerospace University - Widana, I Dewa Ketut Kerta; Setiawati, Sri; Susanto, Primadi Candra (Edelweiss Applied Science and Technology, 2025)
The performance of Dirgantara University Lecturer Marshal Suryadarma (Unsurya) in research and publications places Unsurya, before 2023, in the primary rank. Given the existing conditions, Elemenya leadership has made various improvements to enhance lecturer performance, especially in the fields of research and scientific publications. To improve Tridarma's performance, training assistance activities have been carried out, and after approximately one year, the mentoring program has been successful in raising the middle rank. This research aims to analyze research and publication training to improve lecturer performance in the Tridarma of Higher Education. Using a qualitative approach with descriptive analysis, data collection was carried out through in-depth interviews, observation, and documentation studies. The findings show: (1) Training in research is very important because it helps lecturers understand library observation techniques, identify and plan data source problems, and analyze data using software; (2) publication training improves lecturers' abilities in writing quality articles, citing references using software, introducing reputable publishers, understanding reviewers, and publishing books/journals; (3) These training activities succeeded in improving Tridarma's performance by increasing lecturers' enthusiasm for scientific work, motivation, research and scientific writing competence, and collaboration. This increase can be seen from the rise in research output, publications, intellectual property rights, and affiliations that support lecturer performance reports in accordance with regulations.